Psychometric testing of the persian version of the conditions of work effectiveness Questionnaire-II (CWEQ-II-PV) - Hamidreza Sadeghi-Gandomani; Negin Masoudi Alavi; Mohammad Afshar (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Structural empowerment (SE) is an effective method of advancing work environments and has previously been widely discussed in Western countries. Due to the lack of culturally and academically accepted scales in Iran for measuring SE, localization of a foreign scale in this field is necessary. OBJECTIVES: This study aimed at investigating the validity and reliability of the Persian Version of the Conditions of Work Effectiveness Questionnaire-II (CWEQ-II-PV) among Iranian nurses. METHODS: The present cross-sectional methodological research was conducted during 2017-2018. Participants were 230 nurses working in four teaching hospitals affiliated to Kashan University of Medical Sciences in Kashan, Iran, who were selected using quota sampling. A standard forward-backward translation procedure according to Wild et al. (2005) was used to translate the English Version of the CWEQ-II to Persian. The psychometric evaluation processes were achieved by face, content, and construct validity (confirmatory factor analysis [CFA]). Reliability was examined using test-retest and Cronbach's alpha for internal consistency reliability. RESULTS: The CWEQ-II-PV showed good content validity (the mean content validity scores for relevancy, clarity, and simplicity were 94%, 96%, and 94%, respectively). In the CFA, the original six-factor version with 19 items was confirmed. The original model was presented and incorporated in the CFA, indicating an acceptable fit for the model (root mean square error of approximation = 0.06, comparative fit index = 0.92, goodness of fit index (GFI) = 0.94, and adjusted GFI = 0.91). Cronbach's alpha coefficient for the total scale was 0.84 and for each component ranged from 0.71 to 0.87, indicating good internal consistency, and the test-retest Spearman and intraclass correlation coefficients were 0.93 and 0.87, respectively, showing good test-retest reliability. CONCLUSIONS: Evidence was found to support the reliability and validity of the CWEQ-II-PV scale that measures the quality of the work environment for nurses from a SE perspective.